2005
DOI: 10.1177/1099800405280936
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Exclusive Breastfeeders, Formula-Feeders, and Controls: A Study of Stress, Mood, and Endocrine Variables

Abstract: The purpose of this study was to examine relationships among lactational status, naturalistic stress, mood, and levels of serum cortisol and prolactin and plasma adrenocorticotropic hormone (ACTH). Eighty-four exclusively breastfeeding, 99 exclusively formula-feeding, and 33 nonpostpartum healthy control women were studied. The postpartum mothers were studied cross-sectionally once between 4 and 6 weeks after the birth. Stress was measured using the Perceived Stress Scale, the Tennessee Postpartum Stress Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
93
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 39 publications
12
93
1
2
Order By: Relevance
“…In accordance with the present results suggesting that direct adrenal effects of PRL may be important for steroidogenesis in the response to stress, there are observations from animal studies in which glucocorticoid levels can remain elevated during stress, despite de- clining CRH and/or ACTH concentrations [20,21,[40][41][42]. Previous studies have demonstrated that exercise stress induced an increase in circulating PRL in humans [43][44][45][46][47][48].…”
Section: Discussionsupporting
confidence: 77%
“…In accordance with the present results suggesting that direct adrenal effects of PRL may be important for steroidogenesis in the response to stress, there are observations from animal studies in which glucocorticoid levels can remain elevated during stress, despite de- clining CRH and/or ACTH concentrations [20,21,[40][41][42]. Previous studies have demonstrated that exercise stress induced an increase in circulating PRL in humans [43][44][45][46][47][48].…”
Section: Discussionsupporting
confidence: 77%
“…Our findings indicate that breastfeeding helps enhance a mother's quality of life, with duration of breastfeeding being a key factor. These findings agree with some studies [30][31][32][33][34] and conflict with others [16,17,35,36] that examined the consequences of breastfeeding in areas other than quality of life. Mezzacappa et al found that breastfeeding was associated with fewer gastrointestinal and upper respiratory symptoms and fewer doctor visits [32,37], and Kavanaugh et al reported that mothers of preterm infants perceived specific emotional advantages from their breastfeeding experiences [30].…”
Section: Discussionsupporting
confidence: 72%
“…It is important to note that time of day was included in this analysis, suggesting that the reduction in cortisol was present after taking diurnal changes into account. This reduction of cortisol levels in mothers confirms previous work that has also found a reduction in HPA activity during breastfeeding (Amico et al 1994), and may help inform the finding that breastfeeding mothers generally feel less stressed than bottlefeeding mothers (Groër 2005), and that increased duration of breastfeeding is associated with lower HPA reactivity when faced with a stressful situation (Heinrichs et al 2002). With regard to infant cortisol levels, our hypothesis regarding a general reduction of cortisol was not confirmed.…”
Section: Discussionsupporting
confidence: 78%
“…Critically, in line with the notion that oxytocin reduces stress (de Oliveira et al 2012), breastfeeding results in a strong reduction of hypothalamic-pituitary-adrenal (HPA) axis activity in mothers (for a review, see Heinrichs et al 2002), as reflected in a marked decrease in plasma adrenocorticotropic hormone (ACTH) and cortisol (Amico et al 1994;Handlin et al 2009;Nissen et al 1996). Furthermore, breastfeeding duration has been linked to a range of maternal outcomes such as lower perceived stress levels, reduced anxiety and depressive symptoms, stronger cardiac vagal tone modulation, reduced heart rate reactivity, blood pressure, and reduced HPA activity in response to psychosocial stress (Groër 2005;Hahn-Holbrook et al 2011;Heinrichs et al 2002;Jansen et al 2008;Mezzacappa et al 2005).…”
Section: Introductionmentioning
confidence: 99%